COGNITIVE ABILITY, SOCIAL DESIRABILITY, BODY MASS INDEX, AND SOCIOECONOMIC STATUS AS CORRELATES OF FOURTH-GRADE CHILDREN’S DIETARY-REPORTING ACCURACY - Smith, Albert F. (Eur J Clin Nutr, 2016)
OBJECTIVES: To investigate the relationship of reporting accuracy in 24-h dietary recalls to child respondent characteristics—cognitive ability, social desirability, body mass index (BMI) percentile, and socioeconomic status (SES). SUBJECTS/METHODS: Fourth-grade children (mean age 10.1 years) were observed eating two school meals and interviewed about dietary intake for 24-h that included those meals. (Eight multiple-pass interview protocols operationalized the conditions of an experiment that crossed two retention intervals—short and long—with four prompts [ways of eliciting reports in the first pass].) Academic achievement test scores indexed cognitive ability; social desirability was assessed by questionnaire; height and weight were measured to calculate BMI; nutrition-assistance program eligibility information was obtained to index SES. Reported intake was compared to observed intake to calculate measures of reporting accuracy for school meals at the food-item (omission rate; intrusion rate) and energy (correspondence rate; inflation ratio) levels. Complete data were available for 425 of 480 validation-study participants. RESULTS: Controlling for manipulated variables and other measured respondent characteristics, for one or more of the outcome variables, reporting accuracy increased with cognitive ability (omission rate, intrusion rate, correspondence rate, P < .001); decreased with social desirability (correspondence rate, P < .0004); decreased with BMI percentile (correspondence rate, P = .001), and was better by higher than by lower SES children (intrusion rate, P = .001). Some of these effects were moderated by interactions with retention interval and sex. CONCLUSIONS: Children’s dietary-reporting accuracy is systematically related to such respondent characteristics as cognitive ability, social desirability, BMI percentile, and SES.